Control government oversight reports in Light standards of the International Organization of Supreme Audit Institutions Finance and Accounting (INTOSAI): Evidence from the Iraq State - Al-inizi, Sumaya Mahdi (International Journal of Psychosocial Rehabilitation, 2020)
Aim of this study is to evaluate the commitment of those responsible for preparing oversight reports in the Iraq State by following the requirements of the INTOSAI standards in order to prepare reports in terms of the form, and content of the oversight report and try to adjust from this direction. In the present study the researcher has followed practical modern approach (inductive deductive joint) via examining previous scientific efforts in the field of research phenomenon, as well as the analytical approach to achieve the hypotheses of this research.Importantly, the study concluded that there is a difference in the opinion of the respondents in estimating the benefit criterion for all parties used for monitoring reports. According to that, it follows the content and form in a way that ensures presenting of the results objectively, so that they can utilize these reports in government oversight processes.The study recommended the necessity of adhering to the international standards of the supreme audit bodies when preparing the audit reports in terms of form and content.